Study on the relationship between the resistance to MTX and the transport protein superfamily of ATP-binding cassette that induces multiple drug resistance - Zhang, Chun-Yu; Feng, Yuan-Xi; Li, Pu; Fu, Song-Bin (Yíchuán, 2006)
A major problem, especially the multidrug resistance, in chemotherapy was the resistance to the chemotherapeutic agents. ATP-binding cassette transporter superfamily that mediated the efflux of drugs was involved in multidrug resistance. In order to understand the relationship between the resistance to MTX and the transport protein superfamily of ATP-binding cassette, and to investigate the mechanism of resistance to MTX, the study detected the expressions of mdr1, mrp1, mrp2, mrp3, mrp5, mrp6 and abcg2 that encoded the transport proteins by SuperArray analysis and the expressions of MRP1and MRP5 proteins by Western blot analysis. The results showed that the multidrug resistance proteins were the chief member of ATP-binding cassette transporter superfamily related to resistance to MTX. And the high expression levels of mrp1 and mrp5 were detected. Moreover, it revealed by SuperArray analysis that expression of mrp5 in MTX-resistant cells was significantly higher than that in normal mouse cells. Besides, corre